Crisis de imagen y sanitaria: la tormenta perfecta en el Ecuador del COVID-19 (Ensayos) - Isch Garcés, Gustavo (2023)
Based on a random qualitative exploration of journalistic content, this paper reviews essential narrative axes that connected the image and health crisis from the agenda setting and from social networks, in the public sphere, during the first year of the covid pandemic. -19 in Ecuador. The delimitation of the context in which this process unfolded, and the critical reading of the underlying hegemonic approach in the published information and opinion, have the objective of identifying the communication keys that positioned a collective perception of global crisis, and that even, could have affected the electoral situation of 2021. This research concludes by reflecting on the links that intertwined two specific crises, in a perfect storm.